Perdagangan Manusia Lintas Negara di indonesia - Safa Ega Arfika; Andi Aina Ilmih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Human trafficking is a very serious problem in Indonesia even though the country has endorsed and disciplined the National Action Plan and to form a notion of duty to stop this crime. The phenomenon of human trafficking has become a social fact besides the economic crisis and natural disasters. The low level of education, the limited employment, free relations and acts of harmony in a family are some of the factors causing human trade. Because human trafficking involves an international criminal network, with the participation of all stakeholders through a systematic approach and strengthening the network is a must in preventing and eradicating this. In providing granting legal protection to victims of trafficking in persons, especially restitution issues have been regulated in Article 48 to Article 50 of Law Number 21 Year 2007, also regulated in Article 35 of Law Number 26 of 2000 concerning the Human Rights Court regulates the protection of human rights for human welfare. According to the 1999 Law on Human Rights, as stated in Article 1 states that human rights (HAM) is a set of rights inherent in the nature and existence of humans as almighty gods and is a gift that must be respected, highly respected, and protected by the state, law, government, and everyone for the sake of honor and protection of human dignity.